Does Financial Technology Affect Income Inequality in Indonesia? - Dian Saraswati, Birgitta; Maski, Ghozali; Kalug, David; Kresna Sakti, Rachmad (KnE Social Sciences, 2020)
Economic growth is insufficient to be a sole indicator of the population’s welfare. Specifically, high economic growth does not necessarily imply that the population is generally prosperous. Equal income distribution is crucial to achieving sustainable economic growth. Since 2000, the Gini index as a measure of income inequality in Indonesia showed an increasing trend. On the other side, financial technology 3.0 started to develop. This paper seeks to investigate the impact of fintech 3.0 development on income inequality in Indonesia and to identify the determining factors of income inequality in Indonesia. By using the partial adjustment model (PAM) with the observation period of 1990-2017, the study empirically shows that fintech 3.0 development that started in 2000 had a significant impact on income inequality in Indonesia. Besides, the investment variable also positively affect income inequality in Indonesia. Thus, the findings indicate that the Indonesian population did not equally utilize fintech development. Keywords: income inequality, financial technology, Indonesia, partial adjustment model